The influence of prey density and fish size on prey consumption in common sole (Solea solea L.) - Ende Stephan Siegfried Werner; Thiele Rajko; Schrama Johan W.; Verreth Johan A.J. (Aquatic Living Resources, 2018)
We examined the influence of prey density and fish size on prey consumption in common sole (Solea solea L.) foraging on buried ragworm Alitta virens (Sars) (formerly known as Nereis virens (Sars)). The tested prey densities of 0.8, 2.2, 4.3 and 6.5 individuals dm−2 were exposed to common soles of either 100 g or 300 g. At each prey density common sole foraged for 48 h. At both common sole classes studied, a positive correlation between prey consumption and prey density was observed (P < 0.001). Relationships however differed between 100 and 300 g common sole. In 300 g common sole the relationship between prey consumption and prey density was linear (P < 0.001), whereas in 100 g common sole the relationship between prey density and prey eaten was polynomial (P = 0.018). Small common sole reached satiety prey consumption rates at nearly every prey density while large common sole did not reach satiation rates even at highest prey densities. The data suggest that in nature, polychaetes such as A. virens may contribute to the diet of small common sole even when they are only moderately abundant. In contrast, polychaetes may not be an ideal prey for larger common sole as indicated by the absence of satiety regardless of prey density.